2020
DOI: 10.3390/brainsci10040198
|View full text |Cite
|
Sign up to set email alerts
|

Cognition, The Menstrual Cycle, and Premenstrual Disorders: A Review

Abstract: Sex hormones, such as estrogens, progesterone, and testosterone, have a significant influence on brain, behavior, and cognitive functioning. The menstrual cycle has been a convenient model to examine how subtle fluctuations of these hormones can relate to emotional and cognitive functioning. The aim of the current paper is to provide a narrative review of studies investigating cognitive functioning in association with the menstrual cycle in biological females, with a focus on studies that have investigated cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 86 publications
3
51
0
4
Order By: Relevance
“…Although this study showed one significant correlation between PF task with 45%ROM and water retention in the luteal phase than MDQ alone, previous studies have reported some correlation between menstrual symptoms and cognitive and sensory functions. 59 , 60 To identify the influence of menstrual symptoms on PPI with somatosensory modality and ankle JPS using an active joint position matching method, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study showed one significant correlation between PF task with 45%ROM and water retention in the luteal phase than MDQ alone, previous studies have reported some correlation between menstrual symptoms and cognitive and sensory functions. 59 , 60 To identify the influence of menstrual symptoms on PPI with somatosensory modality and ankle JPS using an active joint position matching method, further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…This theory was applied to MC with the assumption that these “sexually dimorphic” cognitive abilities/skills would differ across MC [ 115 ]. It was therefore expected that women would perform better on visuospatial tasks during phases with low E2 and PG levels and that, in contrast, performance on verbal tasks would be improved during LaF and MiL; in view of recent critical reviews, evidence is nevertheless insufficient to support the sexually dimorphic hypothesis [ 116 , 117 , 118 , 119 , 120 ]. Indeed, regarding visuospatial ability, only a few studies on mental rotation, the most commonly used test [ 120 ], have supported the hypothesis of superior performance in EaF [ 121 , 122 , 123 ], whereas the others showed no significant findings [ 124 , 125 , 126 ].…”
Section: Possible Mechanisms: Performance and Health Risksmentioning
confidence: 99%
“…Elderly men exhibited more atrophy in the left hemisphere, whereas the atrophy was symmetric in elderly women [ 19 ]. Besides normal aging, sex hormones also have a significant influence on alterations of brain structure, behavior, and cognitive functioning [ 20 , 21 , 22 , 23 ]. Postmenopausal women showed significantly decreased gray matter volumes of the insula, putamen, parahippocampal gyrus, amygdala, and anterior cingulate gyrus.…”
Section: Introductionmentioning
confidence: 99%